Dinamika Kesenian Tradisional Angklung Caruk Kabupaten Banyuwangi Tahun 1999-2018 - Arista Nortaviana; sumarno sumarno; rully putri nirmala puji (JURNAL HISTORICA, 2019)
The Angklung Caruk Competition is a unique show. The Angklung Caruk show has indeed become a social habit of the Using community. The word â€œCarukâ€ in Using means â€œgatheringâ€. Angklung Caruk means two Angklung art groups that are brought together into one stage, clashing intelligence with the accompaniment of a number of Banyuwangian songs whose aims to fight for the title as the winner and has been named the best Angklung art group. The Angklung Caruk show is currently full of ethical and aesthetic values. Ethical values appear in a sense of cooperation and sportsmanship. While the aesthetic value appears from the presentation musical works, including all the aesthetic elements such as musical instruments used by melodic, rhythmic, harmony, etc. The musical competition that took place in Angklung Caruk was an interesting phenomenon. Performances become a multifunctional social event, not just a media presentation and enjoyment a piece of music. Angklung Caruk is also a social process that provides an opportunity to show achievement, elevate self-identity, regional groups, strengthen status as well as an arena for social selection of artists. Keywords: Angklung Caruk, Adu Gending